Competition policy in the EU fifty years on from the Treaty of Rome - Vives, Xavier (Oxford : Oxford University Press, 2009)
This is a volume that takes stock & looks ahead on the development & implementation of competition policy in the European Union 50 years after the Treaty of Rome.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Competition -- European Union countries; Antitrust law -- European Union countries